IMPLEMENTASI MODEL PEMBELAJARAN ASSURE PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DI SMP HIDAYATUL UMMAH SURABAYA - ashari, hasim (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2024)
The purpose of this study is, first, to analyze and describe students' learning motivation at SMP Hidayatul Ummah Surabaya; second, to analyze and describe the implementation of the Assure learning model in the subject, Islamic Religious Education at SMP Hidayatul Ummah Surabaya; and, third, to analyze and describe whether the Assure learning model in the subject, Islamic Religious Education can increase student learning motivation at SMP Hidayatul Ummah Surabaya. This was a qualitative research with a case study as the research approach. Data collection techniques in this research was using interviews, observation and documentation. The data analysis technique used was the following steps: data reduction, data presentation, and drawing conclusions. The results of the study concluded that, first, students' motivation at SMP Hidayatul Ummah Surabaya before this study was quite low; second, the implementation of the Assure learning model in the subject, Islamic Religious Education at SMP Hidayatul Ummah Surabaya has been going quite well even though there are still deficiencies; and, third, the Assure learning model in the subject, Islamic Religious Education is proven to be able to increase the student learning motivation at SMP Hidayatul Ummahl Surabaya.